Upaya Meningkatkan Hasil Belajar Pkn Melalui Metode Jigsaw Siswa Kelas VI A SD Negeri 64/IV Kota Jambi Semester Ganjil Tahun Pelajaran 2016/2017 - Aziar Aziar (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
This research is motivated by the fact that students are less active in the class and the learning model used is not appropriate so that the results obtained are not maximal. The low learning outcomes of students in PKn subjects are thought to be caused by a mismatch of learning methods used by teachers in PKN learning. The lecture method commonly used by teachers in teaching is one-way learning, so it tends to make students become passive in learning. The research objectives to be achieved in this study are to improve the PKn learning process so that learning outcomes increase by applying the Jigsaw model of class VI.A Negeri SD 64 / IV Jambi City. This study uses action research as much as two cycles. Each cycle consists of four stages, namely: design, activity and observation, reflection, and revision. The target of this study was class VI A 64 / IV SD Negeri Jambi City. Data obtained in the form of the results of teacher learning management, and student learning outcomes. From the results of the analysis it was found that student learning outcomes experienced an increase from cycle I to cycle II. The Jigsaw model can improve the quality of learning Civics and Jigsaw Model has a positive impact on improving student learning outcomes which is characterized by an increase in student learning completeness in each cycle, namely pre cycle (50.00%), cycle I (65.00%), sklus II (85.00%). The average value of learning outcomes in the first cycle is 71.72 and the second cycle increases to 80.77. While for the management of teacher learning in the first cycle only reached 44.64% and the second cycle increased to 86.61%, and the Jigsaw learning model could be used as an alternative to PKn learning.